Setting up and managing a small hotel - Lim, Lino Ed.; Martin, Patty (Pasig City Anvil, 2008)
"Setting Up and Managing a Small Hotel provides everything the would-be hotelier needs to know--from building the edifice to setting up the management and the organizational structures, defining the duties and responsibilities of each employee, and setting out the policies and procedures for each department. The book also gives previews of how key departments work around the clock, sample forms used in daily operations and tips to achieve guest satisfaction. This is a valuable textbook for students and a must-have guide for people looking to build a career in the hospitality industry.--Joseph H. Durano"--Back cover.
Chapter 1. The history of the Philippine hospitality industry / by Lino Ed. Lim -- Chapter 2. Conducting a feasibility study / by Lino Ed. Lim -- Chapter 3. The importance of location / by Lino Ed. Lim -- Chapter 4. Constructing a hotel / by Lino Ed. Lim -- Chapter 5. Financing your hotel / by Lino Ed. Lim -- Chapter 6. Setting up the business / by Lino Ed. Lim -- Chapter 7. The management of a small hotel / by Danilo M. Molina -- Chapter 8. The resident manager / by Danilo M. Molina -- Chapter 9. The security department / by Ramon Panday ; with Quirico Banan -- Chapter 10. The engineering department / by Bert Sumagaysay -- Chapter 11. The housekeeping department / by Patty Martin ; with Sisie Alba, Ram Manansala and Rico Carandang -- Chapter 12. The front office / by Priscilla Resurreccion, Elma C. Biteng and Danilo M. Molina -- Chapter 13. The human resources department / by Rhea Suiza, Maricel Maycong and Chrisanta Oliveros -- Chapter 14. The food and beverage department / by Cynthia Balindoa, Ching Castro, Jess Binauhan and Minda Bernal -- Chapter 15. The sales and marketing department / by Ghie Gomez and Anne Dizon -- Chapter 16. The finance department / Connie Arles ; with Cecilia Soriano, Yolly Valderrama, Isabelita Teodoro and Alma Lim -- Chapter 17. Results of management survey / by Lino Ed. Lim -- Appendix A : Department of Tourism accreditation -- References -- Topical index -- Charts and forms index.
Keywords: Hotel management; Hospitality industry -- Management; New business enterprises -- Management